Implementasi Supervisi Kepala Sekolah Dalam Meningkatkan Pembelajaran Efektif Bagi Guru Di SD Negeri Pabelan 03 Kartasura - Setyawan, Pandhu Abdi Mega, Dra. Risminawati, M.Pd (2017)
This study aims to describe the principal role in the supervision of teacher learning, factors restricting, and solutions to overcome the barrier factors in supervised learning. This research uses qualitative research with a descriptive qualitative approach. Using data collection techniques interviews, observation, and documentation. While the validity of the data using triangulation techniques and sources. The results showed that: (1) the principal SD Negeri Pabelan 03 in carrying out his duties as a supervisor to enhance effective learning is already well underway. Prior to the implementation of the supervision, the principal planning first, then inform teachers, it aims to help teachers in perceived their tasks well. (2) there is an inhibitor factors i.e. time and many teachers that awkward time of supervision was held. (3) a solution to overcome the barrier to supervision factors, among others: (a) the principal rearrange the schedule of supervision. (b) the principal holding of observation learning outside of the classroom. Keywords : supervision, head of school, effective learning